Blood Lipid Components and SREBP-1 Gene Expression in Broiler Chickens Fed Different Dietary Lipid Sources - Moslehi, Amir; Sadeghi, Ali Asghar; Shawrang, Parvin; Aminafshar, Mehdi (Acta Scientiae Veterinariae, 2016)
Background: Liver plays an important role in energy homeostasis. Intense liver diseases are accompanied with lower concentrations of n-3 and n-6 poly unsaturated fatty acids (PUFA). It has been found that n-3 PUFA play importantly protective roles in the liver. There was limited information about the effects of lipid sources on serum lipid components and liver sterol regulatory element binding-1 (SREBP-1) gene expression. Therefore, the aim of this study was to evaluate and compare the effects of fish oil, corn oil, olive oil and tallow, respectively, as dietary sources of n-3, n-6, n-9 and saturated fatty acid on serum lipid compound and liver SREBP-1 gene expression in broiler chicks. Materials, Methods & Results: In a completely randomized design, 240 one-day-old broiler chicks were allocated to five dietary treatments, four replicates and 12 chicks per each. Dietary treatments included of: control (diet without lipid supplementation) and diet supplemented with fish oil as a n-3 fatty acid source, corn oil as a n-6 fatty acid source, olive oil as a n-9 fatty acid source and tallow as a saturated fatty acid which were added to diets at 1.5, 3 and 4% in the starter, grower and finisher, respectively. At days 28 and 42 of age, liver tissue was dissected out and samples were placed in liquid nitrogen, also blood samples were collected. The SREBP-1 mRNA expression in liver tissue was quantitated using RT-PCR. Broilers fed diets containing fish oil, corn oil and olive oil as unsaturated fatty acid sources had lower concentrations of triacylglycerol than those fed other diets. Also, diets containing fish oil and tallow showed the lowest low density lipoprotein (LDL) levels at day 28 of age. Diets containing corn oil and olive oil showed higher levels of cholesterol and high density lipoprotein (HDL) than other diets but, these differences were not significant at days 28 and 42 of age (P ≥ 0.05). In both sampling periods, the chickens fed diets containing tallow expressed higher (P < 0.05) SREBP-1 gene as compared to those fed other dietary lipids. Broilers fed diet containing corn oil had higher (P < 0.05) SREBP-1 gene expression than those fed diet containing fish oil and olive oil. Discussion: Serum lipids were affected by dietary fat source. Lower concentration of serum triacylglycerols was found in broilers fed fish oil and corn oil diets as dietary n-3 and n-6 fatty acid sources. It was shown that dietary PUFA, especially n-6 and n-3 fatty acids could reduce hepatic fatty acid and triacylglycerol synthesis. Broilers fed corn oil diet showed elevated LDL levels respect with those fed fish oil or tallow at day 28 of age. The results showed that dietary polyunsaturated fatty acids and saturated fatty acids substantially affected on SREBP-1 gene expression at days 28 and 42 of age. The birds fed fish oil as n-3 PUFA source expressed lower SREBP-1 gene compared with other groups at day 28 of age. Longer chain length, high number of double bonds, and the presence of the first double bond gives these fatty acids distinct and unique properties that separate them and their metabolic products from the more common n-6 and n-9 fatty acids. The finding of this study indicated lipogenic effects of tallow and then corn oil. The results confirmed that each of dietary lipid sources had different effect on serum lipid components. It was also found that SREBP-1 gene expression is age-dependent and it increased as age of broilers increased.